The Department of Tourist and Health Resorts and the Creation of the "Finest Walk in the World" - Jacobs, Jamie (Architectural History Aotearoa, 2025)
The Milford Track – dubbed "the Finest Walk in the World" as early as 1908 – stands among New Zealand's most significant and best-known tourism destinations. This moniker stems from a combination of the exhilarating natural beauty encountered along the track as well as its essential visitor facilities that were developed and sustained for tourism. It was in the first decades of the twentieth century that the Milford Track, along with other places of cultural and natural interest, established tourism as an essential component of national pride, identity, and the burgeoning economy of colonial New Zealand. This paper will explore the establishment of the Milford Track with a particular focus on the development of the walking path and its facilities, and how they contributed to the creation of an early, codified visitor experience that has remained remarkably consistent for well over a century.